I45 Alternative medicine methods utilisation in huntington's disease. (13th September 2016) - Zielonka, Daniel; Puch, Elżbieta A
Abstract : Background: Alternative therapy is a common therapeutic approach in general population (GP). It was never analysed in details in HD subjects. Aim: The aim of the study was to characterise alternative medicine methods application in individuals affected by Huntington's disease (HD). Material and methods: We used HD cohort from REGISTRY Study Site of Poznań, Poland to screen for individuals who utilised alternative medicine methods. Based on demographic data from Polish population we were able to compare alternative medicine methods utilisation (AMMU) in age and gender matched HD cohort and GP. Analysis was stratified by such alternative methods as homeopathy, herbal, acupuncture and other. Moreover HD cohort representatives utilising alternative medicine method were characterised in detail. Results: In 57 representatives of Poznań Study Site's HD cohort we found 3 patients utilising alternative medicine methods. Comparing our HD group with Polish GP we found significantly higher prevalence of AMMU (HD 5.2% vs. GP 1.8%). In our HD patients AMMU was represented by: herbal medicine, homeopathy and bioenergotherapy. All HD subjects were married men at the education level ISCED–3, motor manifest, who started AMMU in a year of clinical diagnosis. Motor, cognitive, functional and behavioural impairment in all three subject was on very similar level when AMMU was declared at study visit. Conclusion: Based on the results of the study, AMMU widespread in HD affected individuals seems to be higher than in general population. Probably it results from lack of cure for HD. Expected trigger of AMMU is the moment of HD clinical diagnosis, when still cognitively competent patients become consent of fatal HD outcome and lack of conventional medicine response for their health needs.